Managing Ammonia Emissions from Dairy Cows by Amending Slurry with Alum or Zeolite or by Diet Modification - John J. Meisinger; Alan M. Lefcourt; Jo Ann S. Van Kessel; Victor Wilkerson (The Scientific World Journal)
Animal agriculture is a significant source of atmospheric ammonia. Ammonia (NH3) volatilization represents a loss of plant available N to the farmer and a potential contributor to eutrophication in low-nitrogen input ecosystems. This research evaluated on-farm slurry treatments of alum or zeolite and compared three diets for lactating dairy cows in their effectiveness to reduce NH3 emissions. NH3 emissions were compared using a group of mobile wind tunnels. The addition of 2.5% alum or 6.25% zeolite to barn-stored dairy slurry reduced NH3 volatilization by 60% and 55%, respectively, compared to untreated slurry. The alum conserved NH3 by acidifying the slurry to below pH 5, while the zeolite conserved ammonia by lowering the solution-phase nitrogen through cation exchange. The use of alum or zeolite also reduced soluble phosphorus in the slurry. NH3 loss from fresh manure collected from lactating dairy cows was not affected by three diets containing the same level of crude protein but differing in forage source (orchardgrass silage vs. alfalfa silage) or neutral detergent fiber (NDF) content (30% vs. 35% NDF). NH3 losses from the freshly excreted manures occurred very rapidly and included the urea component plus some unidentified labile organic nitrogen sources. NH3 conservation strategies for fresh manures will have to be active within the first few hours after excretion in order to be most effective. The use of alum or zeolites as an on-farm amendment to dairy slurry offers the potential for significantly reducing NH3 emissions.